2007
DOI: 10.1002/ejic.200601235
|View full text |Cite
|
Sign up to set email alerts
|

Metallated Phthalocyanines as the Core of Dendrimers – Synthesis and Spectroscopic Studies

Abstract: The complexation of a first‐generation dendrimer possessing a metal‐free octasubstituted phthalocyanine as its core has been carried out with copper and cobalt chlorides. In the case of the cobalt complex, the synthesis of the dendrimer has been pursued up to the eighth generation. The progressive influence of the branches upon the core has been studied with dendrimers from generation 1 to generation 7, using UV/Vis spectroscopy. These data indicate a progressive isolation of the core.(© Wiley‐VCH Verlag GmbH … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
1
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 22 publications
0
17
1
1
Order By: Relevance
“…Their non‐degenerate LUMO orbitals manifested themselves as a split band in the long‐wavelength UV/Vis region. As shown in the study by Leclaire et al., the presence of bulky dendritic substituents in the periphery of a macrocycle is responsible for shielding the tetrapyrrolic core and thus for an increase in the Q‐band intensity with every dendrimer generation added. In our study, the relative absorbance of the Q band of tribenzoporphyrazines 9 and 13 with G 0 and G 1 dendrimeric substituents of different size did not change significantly.…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…Their non‐degenerate LUMO orbitals manifested themselves as a split band in the long‐wavelength UV/Vis region. As shown in the study by Leclaire et al., the presence of bulky dendritic substituents in the periphery of a macrocycle is responsible for shielding the tetrapyrrolic core and thus for an increase in the Q‐band intensity with every dendrimer generation added. In our study, the relative absorbance of the Q band of tribenzoporphyrazines 9 and 13 with G 0 and G 1 dendrimeric substituents of different size did not change significantly.…”
Section: Resultsmentioning
confidence: 94%
“…The possibility to add and modify dendrimer substituents at the periphery of macrocyclic rings has been applied so far for porphyrins and phthalocyanines . It has been shown that dendrimeric moieties around the porphyrinoid core significantly affect their photophysical characteristics . Dendrimers by themselves are highly branched polymers with unique physico‐chemical and biological properties .…”
Section: Introductionmentioning
confidence: 99%
“…A phthalocyanine functionalized by eight aldehydes has been used as core for the synthesis of phosphorhydrazone dendrimers, using the process shown in Scheme 1. The process was carried out up to generation 5 from a free phthalocyanine, and up to generation 8 starting from its cobalt complex [10]. The phthalocyanine core was used for analyzing the properties of the internal structure and for determining the influence of each structural part (surface, branches, core) upon the whole structure, behaving as a sensitive sensor.…”
Section: Functional Cores Of Dendrimers (Type A)mentioning
confidence: 99%
“…Dendrimers of up to the eighth generation complexed with Co(II) were prepared to study the progressive influence of the branches on the core (Fig. The addition of subsequent generations did not show any further change, indicating that the influence of the branches on the core is limited up to this specific generation probably due to steric hindrance [44]. The addition of subsequent generations did not show any further change, indicating that the influence of the branches on the core is limited up to this specific generation probably due to steric hindrance [44].…”
Section: Porphyrin and Phthalocyanine-based Dendrimersmentioning
confidence: 99%